Manejo agronómico de citrus reticulata blanco variedad w. murcott en chao - La Libertad - Acevedo Alfaro, Rodolfo Hernán (2016)
The aim of this study was to describe the agronomic crop management tangerine W. Murcott variety in the company Camposol, Chao - La Libertad. Soil preparation for installation of the crop requires good subsoiling and gradeo for proper root development. Mandarin seedlings are obtained from certified nurseries. The planting has spacings of 6 x 4 m, which are obtained 417 plants per hectare. Fertilization at the beginning of the crop carries a composting background; subsequently to the growth and development of plants, fertigation the following units are applied: 40 N, 10 P2O5, 15 K2O, 11 CaO and production fields are the following units: 126.5 N, 53.6 P2O5, 115.2 K2O, and 54.2 CaO in the first campaign. The drip irrigation is performed using 2000-3000 m3 of water installation and 4000-7000 m3 in production. During the growing season weed infestation as purslane, sow thistle, nightshade and dairy is presented, which is controlled by hand weeding in installing and using herbicide Glyphosate to 1% in production fields; likewise two prunings, a training and other production, are made to be both very important. The most important phenological stages are swollen bud, early bud, sprouting, bud growth. For phytosanitary control pesticide applications and biologicals that can be applied by machine or lever backpack are made. Harvesting is done at 36 months of age of the crop when the fruits are physiologically mature and a uniform orange color, yields in the area are 10 to 15 tn.ha - 1 in the first campaign